A bilateral teleoperation with interaction force constraint in unknown environment using non linear model predictive control. (November 2021) - Piccinelli, Nicola; Muradore, Riccardo
Abstract: In critical scenarios, the interaction forces between a robot and the environment could lead to damages and dangerous situations. Complex tasks like grasping fragile objects or physical human-robot interaction in collaborative robotics require the capability of controlling forces. In bilateral teleoperation, force feedback is used to provide telepresence to the operator. In such situation, the force is commonly measured by a force/torque sensor at the end effector of the remote robot. Even if force feedback allows the operator to feel the interaction with the environment this does not prevent unsafe motion. In this paper, we propose a model predictive control (MPC) based bilateral teleoperation able to guarantee safe interaction with the environment by constraining the forces. The method does not assume any prior knowledge of the environment.